Researching professional English as a foreign language lecturer in the industry 4.0: A curriculum perspective - Habiburrahim Habiburrahim; Saiful Akmal; Ika Kana Trisnawati; Suryanto Suryanto; Maira Mustiranda; Safrul Muluk (Institute of Advanced Engineering and Science, 2022)
The issue of professional English as a foreign language (EFL) lecturer in the industrial revolution 4.0 (IR 4.0) era has received considerable attention. However, very few studies on this subject have been conducted in Indonesia, particularly at State Islamic Universities. To address this gap, researchers conducted a qualitative study to examine how EFL lecturers maintain their professionalism in the IR 4.0 era and the curriculum approach that best meets current teaching and learning needs. The researchers applied a purposive sampling approach in selecting the participants for this study. There were 11 EFL lecturers from a state Islamic university in Banda Aceh, Indonesia chosen to participate in this study. The findings of this study indicate that EFL lecturers must continue to learn and improve their digital and technological competency in order to maintain their professionalism. In terms of curriculum approach, EFL lecturers believe that taking an interdisciplinary approach and providing more opportunities for students to focus on applied skills are essential parts of their teaching professionalism in the IR 4.0 era.